Organization and function of an actin cytoskeleton in Plasmodium falciparum gametocytes. (31st October 2014) - Hliscs, Marion; Millet, Coralie; Dixon, Matthew W.; Siden‐Kiamos, Inga; McMillan, Paul; Tilley, Leann
Summary In preparation for transmission to its mosquito vector, Plasmodium falciparum, the most virulent of the human malaria parasites, adopts an unusual elongated shape. Here we describe a previously unrecognized actin‐based cytoskeleton that is assembled in maturing P. falciparum gametocytes. Differential extraction reveals the presence of a highly stabilized population of F‐actin at all stages of development. Super‐resolution microscopy reveals an F‐actin cytoskeleton that is concentrated at the ends of the elongating gametocyte but extends inward along the microtubule cytoskeleton. Formin‐1 is also concentrated at the gametocyte ends suggesting a role in actin stabilization. Immunoelectron microscopy confirms that the actin cytoskeleton is located under the inner membrane complex rather than in the sub‐alveolar space. In stage V gametocytes, the actin and microtubule cytoskeletons are reorganized in a coordinated fashion. The actin‐depolymerizing agent, cytochalasin D, depletes actin from the end of the gametocytes, whereas the actin‐stabilizing compound, jasplakinolide, induces formation of large bundles and prevents late‐stage disassembly of the actin cytoskeleton. Long‐term treatment with these compounds is associated with disruption of the normal mitochondrial organization and decreased gametocyte viability.